Preparo e caracterização de carvão ativado impregnado com goetita e magnetita para remoção de corantes por ação combinada de adsorção e oxidação - Bragião, Maria Eduarda (2019)
In this work, precipitation methods of the iron oxides goethite (α-FeOOH) and magnetite (Fe3O4) were applied for the preparation of two composites (CA / GOE and CA / MAG) and the removal of Reactive Black 5 (RB5) dye was evaluated through the adsorption / oxidation process in the presence of hydrogen peroxide (H2O2). Activated carbon (CA0) and composites were characterized by scanning electron microscopy (SEM), dispersive energy spectroscopy (EDS), N2 isotherm adsorption / desorption, Fourier transform infrared (FTIR) and X-ray diffraction. (DRX). The micrographs obtained by SEM showed that the morphology of the composites presented with changes when compared to the porous morphology of activated carbon. EDS analysis revealed the presence of carbon (C), oxygen (O) and iron (Fe). The mapping shows that these elements are not distributed evenly in the analyzed region. FTIR results showed the presence of α-FeOOH on the surface of the CA / GOE composite at a concentration of 4.23 mg g-1, and the α-FeOOH and Fe3O4 oxides precipitated at CA / MAG withx a concentration of 30.77 mg. g-1. The composites were microporous with some mesoporosity. Adsorption / oxidation tests applying CA0, CA / GOE and CA / MAG in the presence of H2O2 were performed at pH 3 and 6, with the highest RB5 discolourations obtained at pH 3 for all samples. The discoloration of RB5 to CA0 at pH 3 occurred by adsorption / oxidation and at pH 6 was predominantly by adsorption. For CA / GOE and CA / MAG composites, RB5 discolouration was observed through the combined action of adsorption / oxidation at both pH 3 and 6. CA / GOE was more active than CA / MAG reaching 94.14% in RB5 discoloration at pH 3.